Analysis of CT Scans Findings in Seizures Patients: An Observational Study - Bapu saheb Patil, Niranjan; Dashrath Wadhwani, Nitin (Asian Journal of Medical Radiological Research, 2019)
Background: Seizures may occur in up to 10% of the population. There is general consensus that adults with an unprovoked first seizure should have brain imaging with either CT or MRI primarily to identify any process that may be responsible for the seizure. Hence; under the light of above mentioned data, the present study was planned for assessing CT scans and their findings in seizures patients. Subjects and Methods: All the patients reporting with the history of seizure disorder were admitted to the emergency department and were treated accordingly. Complete past medical and clinical history of all the patients was obtained. In all the patients, EEG was done and findings of the EEG were correlated with the final diagnosis. In all the patients CT scan was done. Diagnosis was confirmed after correlating the clinical findings of all the patients with clinical history and microbiological investigation reports. All the results were analyzed by SPSS software .Results: Tuberculoma was found to be present among in 18 patients with partial seizures. Cerebral infarct was found to be present in 10 patients with partial seizures and among 15 patients with generalized seizures. Focal cerebral edema was found to be present in 10 patients with partial seizures. Diffuse cerebral edema was found to be present in 13 patients with generalized seizures. Brain tumour was found to be present among 6 patients with partial seizures. Calcifications were found to be present in 4 patients with partial seizures and 10 patients with generalized seizures. Conclusion: CT is sensitive for detection of neural lesions and is advocated in seizure patients. However; further studies are recommended.